2019
DOI: 10.1039/c9ra00839j
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of hydroxyapatite, fluor-hydroxyapatite and Si-substituted hydroxyapatite nanoparticles on osteogenic, osteoclastic and antibacterial ability

Abstract: This study compared the effects of hydroxyapatite (HA), fluor-hydroxyapatite (FHA) and Si-substituted hydroxyapatite (SiHA) on osteogenic differentiation, osteoclastic activity and antibacterial properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 87 publications
0
8
1
1
Order By: Relevance
“…It can be observed that all characteristic peaks of fluorapatite, P2p, and Ca2p, at 133.2 and 347.2 eV, respectively [ 30 ], were detected in the F 0.1 coating. Looking in detail, it can be observed one additional small peak at ~684.3 eV, belonging to F1s, indicating that F − ions were incorporated into the fluorapatite lattice structure [ 31 , 32 ]. The F/Ca ratio, calculated directly from the XPS data, was F/Ca = 0.182.…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that all characteristic peaks of fluorapatite, P2p, and Ca2p, at 133.2 and 347.2 eV, respectively [ 30 ], were detected in the F 0.1 coating. Looking in detail, it can be observed one additional small peak at ~684.3 eV, belonging to F1s, indicating that F − ions were incorporated into the fluorapatite lattice structure [ 31 , 32 ]. The F/Ca ratio, calculated directly from the XPS data, was F/Ca = 0.182.…”
Section: Resultsmentioning
confidence: 99%
“…23 Thus, variation in the crystallite size significantly influences the properties of the materials. To measure the crystallite size, the data of XRD are widely utilized, and Scherrer's equation is generally used 24 which is expressed here in eqn (2), and the computed crystallite sizes are documented in Table 2. When highenergy gamma radiation was applied through the HAp samples, there was a linear change of crystallite sizes within the 20-80 kGy gamma radiation doses.…”
Section: Specific Surface Areamentioning
confidence: 99%
“…2 It is being widely used as a potential bone graft substitute material in orthopedic and dentistry fields, 3 and thus controlling its properties is very crucial for fruitful applications, notably 2.2 million people need bone grafting per year. 2 Crystallite size and shape are important for the biomimetic application of materials in the body along with controlling degradation properties. 4 In addition to the biomedical application, HAp has been widely used in various fields such as wastewater treatment, 5 therapeutic ion delivery, 6 photocatalytic degradation, 7 etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu çalışmada SiHA için % 1,63 ağırlıkça Si ilavesi yapılmıştır. Oranın fazla olduğu çünkü elektro-kimyasal kaplama ile sağlanan 3 boyutlu yüzeyin fazla Si birikimine yol açtığı ve bunun da sitotoksisiteye neden olduğu düşünülmektedir[135][136].HA yüksek biyo-uyumluluğu ve osteokondüktif özelliği sayesinde klinik uygulamalarda tercih edilen bir biyo-seramik malzemedir. Fakat stokiyometrik HA, yeni kemik dokusunun gelişimini teşvik etmek ve ara yüzler oluşturmak için sınırlı bir yeteneğe sahiptir.…”
unclassified